Molecular epidemiology of macrolide resistant Group A streptococci from Puducherry, India - Tintu Abraham; Sujatha Sistla (Journal of Infection in Developing Countries)
Introduction: In penicillin allergic patients, macrolides are the most commonly used antibiotics for treating streptococcal infections, irrespective of the higher resistance rates. The objective of this study was to evaluate the comparative prevalence, phenotypes, and genetic determinants of macrolide resistance and associated emm types among different clinical isolates of Streptococcus pyogenes.